Prevalence and treatment preference of burnout, depression, and anxiety among mental health professionals in Saudi Arabia - Ahmad N AlHadi; Mohammad Ibrahim Almutlaq; Mohammed K Almohawes; Abdulaziz M Shadid; Abdulaziz A Alangari (Wolters Kluwer Medknow Publications, 2022)
Background: Mental health workers face a lot of stressors in their jobs. This issue has been addressed widely by researchers as a major factor predisposing these professionals to many mental health disorders. However, there is limited research addressing the prevalence of these disorders and their treatment preferences among mental health professionals (MHPs) in Saudi Arabia. Aims: This study aims to assess the prevalence and treatment preference of depression, anxiety, and burnout among MHPs in Saudi Arabia. Methods: In this cross-sectional study, MHPs in Saudi Arabia were approached to participate in the study. A self-administered online survey was administered with questions on basic demographics, treatment preference, and three scales that assessed burnout (the Maslach Burnout Inventory), depression (Patient Health Questionnaire-9), and anxiety (Generalized Anxiety Disorder-7). SPSS version 22.0 was used to perform the analysis. Results: A total of 1,253 surveys were completed (59.8% by women); most respondents were psychologists (72.5%). Burnout was the most prevalent in our sample (42.7%), followed by depression (21%) and anxiety (19%). Psychiatrists were more likely to suffer from emotional exhaustion than other MHPs. Women were significantly more likely to develop anxiety and depression than men. For (37%) of the psychologists and similarly (36.65%) of the psychiatrists, making decisions about inpatient treatment was influenced by confidentiality or stigma. Conclusion: Burnout, depression, and anxiety are prevalent among MHPs. Implementing strategies to overcome these issues are vital to improve their well-being and maintain the provision of high-quality mental health care to their patients.